Da arqueologia de gênero e sexualidade à arqueologia pública: sobre as representações das romanas - Silva, Camila Dos Reis (2018)
The present work is a historiographical research whose objective is to reflect how the women were represented in Roman material cultures. Therefore, we will establish a dialogue with Archeology. We intend, through the use of the spintriae coins, that they have coinage of sexual practices, originating from the roman principality, to analyze the imagery representations of the women realized by the male romans. We will employ an interdisciplinary approach, in which iconography and Archeology will be analytical instruments of the coins, and Historiography to contextualize the temporality and the characters studied. After the data collected, we will try to understand the senses of the feminine imagery presentations by the Roman men and their possible social indications. Based on the Public Archeology, as an object of learning, through the RPG Maker program, we will create an escape game set in a virtual museum. The objective is to make the characters escape from the museum. To pass from each stage / game room / museum, the player / student must solve pedagogical activities that refer to the research theme.